2016
DOI: 10.11646/phytotaxa.247.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Ligninsphaeria jonesii gen. et. sp. nov., a remarkable bamboo inhabiting ascomycete

Abstract: A new ascomycete species, inhabiting decaying bamboo culms, is introduced in this paper based on morphology and molecular evidence. Analyses of partial LSU sequence data place the taxon in a monophyletic clade within the order Pleosporales. Morphological characters of the taxon are also distinct from other members of Pleosporales. Ligninsphaeria jonesii gen. et sp. nov. is therefore introduced to accommodate the new taxon, which is characterized by its clypeate, scattered, deeply immersed ascomata, with a slit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…However, Striatiguttulaceae differs from Pseudoastrosphaeriellaceae as the latter has 1–3-septate or 2–5-septate ascospores, which are narrowly fusiform with acute ends and all cells are concolorous. The slit-like ascomata and broad fusiform, 1-septate, rather large ascospores (79–121 × 14–23 µm) in Ligninsphaeriaceae (Zhang et al 2016) are distinct from those found in Striatiguttulaceae. Additionally, a divergence time estimate analysis indicated that the crown age 39 (20–63) MYA and stem age 60 (35–91) MYA of Striatiguttulaceae, match with the recommendations of using divergence times to recognize families in Liu et al (2017).…”
Section: Resultssupporting
confidence: 60%
“…However, Striatiguttulaceae differs from Pseudoastrosphaeriellaceae as the latter has 1–3-septate or 2–5-septate ascospores, which are narrowly fusiform with acute ends and all cells are concolorous. The slit-like ascomata and broad fusiform, 1-septate, rather large ascospores (79–121 × 14–23 µm) in Ligninsphaeriaceae (Zhang et al 2016) are distinct from those found in Striatiguttulaceae. Additionally, a divergence time estimate analysis indicated that the crown age 39 (20–63) MYA and stem age 60 (35–91) MYA of Striatiguttulaceae, match with the recommendations of using divergence times to recognize families in Liu et al (2017).…”
Section: Resultssupporting
confidence: 60%
“…More precise morphological examination of both sexual and asexual morphs in this family will be needed to define familial concepts of Lophiotremataceae and its relatives. The phylogenetic significance of slit-like ostioles of ascomata should also be re-evaluated because this phenotypic character is now known in several families, such as Aigialaceae ( Suetrong et al 2009 ), Ligninsphaeriaceae ( Zhang et al 2016 ), and Lophiostomataceae ( Thambugala et al 2015 ). The slit-like ostiole should be regarded as a character that has evolved multiple times independently within Dothideomycetes , similar to the parallel evolution of hysterothecial ascomata in Anteagloniaceae ( Mugambi & Huhndorf 2009 ), Gloniaceae ( Boehm et al 2009 ), Hysteriaceae ( Boehm et al 2009 ), Lophiostomataceae ( Thambugala et al 2015 ), and Mytilinidiaceae ( Boehm et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is evident from the numerous new species being described from Asia and South America ( Hyde et al 2018 , 2019a , 2020 ). With this in mind, we are studying the fungi of the Karst regions in China and Thailand, where we are also finding numerous new species ( Zhang et al 2016 , 2017a , b , 2018 , 2019 ). Our study is contributing to the knowledge of fungal diversity in the region, where species may also have biotechnological potential ( Hyde et al 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it would be interesting to study the fungi in this area because of its unique ecological environment and rich plant resources. A series of studies have already been carried out and yielded several new species ( Zhang et al 2016 , 2017a , b , 2018 , 2019 ). The objectives of this study are to introduce four novel species of Rhytismataceae , based on phylogenetic and morphological evidence and elucidate their affinities with related species.…”
Section: Introductionmentioning
confidence: 99%